PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS ETHNO MATHEMATICS TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA - Jaja Rusja; Abdul Rosyid; Uba Umbara (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
Implementation of Contextual Teaching and Learning(CTL) Model Based on Ethno Mathematics on Students' Mathematical CreativeThinking Skill, Mathematics Education Study Program STKIP MuhammadiyahKuningan, 2017. Lack of creative thinking ability in learning process causes thedevelopment of the child's mindset becomes shackled and can decrease the creativityof students, whereas the ability to think creatively mathematically students is one ofthe abilities that must be possessed in learning mathematics. From the results it isknown that the mean of the control class score is 76.24 and the experimental class is81.24. Through t test on the value is known that the value of t count = 2.28. While at5% freedom level is known ttabel = 1,998. From both data we know that thitung>ttabel is 2.28> 1.998, then H1 accepted. This means that the average final test resultbetween the experiment class and the control class is different. This means that afterthe treatment of mathematical creative thinking ability of the experimental classstudents is better than the control class. The ability to think creatively mathematicallyexperimental class students are in the high category.